2004
DOI: 10.1080/10635150490522340
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetics of Squamata: The Position of Snakes, Amphisbaenians, and Dibamids, and the Root of the Squamate Tree

Abstract: Squamate reptiles (snakes, lizards, and amphisbaenians) serve as model systems for evolutionary studies of a variety of morphological and behavioral traits, and phylogeny is crucial to many generalizations derived from such studies. Specifically, the traditional dichotomy between Iguania (anoles, iguanas, chameleons, etc.) and Scleroglossa (skinks, geckos, snakes, etc.) has been correlated with major evolutionary shifts within Squamata. We present a molecular phylogenetic study of 69 squamate species using app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
408
9
26

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(498 citation statements)
references
References 100 publications
55
408
9
26
Order By: Relevance
“…In addition, the clustering of the chicken eggshell with the rigid-shelled Geckos argues further that the differences observed in eggshell composition is an adaptation and not an artifact of common ancestry. The placement of snakes, all with flexible eggshells, within the flexible shelled lizards is consistent with both an adaptive explanation (all have flexible eggshells) and a phylogenetic one (see Townsend et al, 2004).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, the clustering of the chicken eggshell with the rigid-shelled Geckos argues further that the differences observed in eggshell composition is an adaptation and not an artifact of common ancestry. The placement of snakes, all with flexible eggshells, within the flexible shelled lizards is consistent with both an adaptive explanation (all have flexible eggshells) and a phylogenetic one (see Townsend et al, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…Eggshell composition was shown to have a significant genetic composition, and, thus, it is possible that the differences observed are due to genetic relatedness and not to environmental adaptation. Recent phylogenetic analysis of the squamate reptiles places the Gekkoniidae and the Eublepharidae in a clade distinct from other squamates (Townsend et al, 2004). The eggshells of the two species of Eublepharidae in this study cluster with the other flexible shelled squamates and not with the more closely related Gekkoniidae.…”
Section: Discussionmentioning
confidence: 45%
“…Moreover, their bizarre external appearance, acrodont dentition, unique skeletal anatomy, as even their specialized feeding and locomotor habits have long lead herpetologists to consider chameleons as a monophyletic group (Camp 1923;Estes 1983). Their relationships to other squamates, however, are yet not fully resolved, mostly because of the uncertainty of the position of Iguania, but it is widely accepted that Chamaeleonidae constitute a group within the iguanian clade Acrodonta (Estes et al 1988;Townsend et al 2004;Kumazawa 2007;Conrad 2008;Vidal and Hedges 2009;Gauthier et al 2012;Wiens et al 2012;Pyron et al 2013; Electronic supplementary material The online version of this article contains supplementary material et al 2015), even if their affinities with Agamidae are a matter of debate, with different topologies arising on the basis of morphological and molecular data (Bolet and Evans 2013;Tolley and Menegon 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This discovery was built upon two higher-level genetic studies aimed to solve phylogenetic conflicts within Squamata (Vidal and Hedges, 2004;Townsend et al, 2004). These studies suggested that previous morphology-based phylogenetic relationships are incorrect in positionining Iguania as a sister group to the rest of squamates.…”
Section: Toxicoferamentioning
confidence: 99%
“…Both Mackessy and Sweet also relied heavily upon Hargreaves tissue expression paper (Hargreaves et al, 2014) for their interpretation. For the exact differences between the traditional and Toxicofera phylogenetic approaches we recommend looking into dedicated studies (Streicher and Weins, 2016;Mackessy et al, 2016;Jackson et al, 2016;Zheng and Weins, 2016;Vidal and Hedges, 2009;Townsend et al, 2004). …”
Section: Toxicoferamentioning
confidence: 99%